Labour conciliation: an analysis on its functionality as a dispute resolution system - Matallana Ruiz, Roberto (2019)
Inherent to human socialization, dispute does not escape labor relations. Based upon an unequal status between employer and worker, labor relations off er a constant battle of opposing interests. Therefore, its resolution is the challenge to face. Among the current predominance of pacific dispute resolution, conciliation is an alternative to consider before a labor dispute. This article aims to analyze conciliation as a system of labor dispute resolution by using dispute theory to defi ne labor dispute and its different forms. Furthermore, the article displays the diversity of dispute resolution systems, specifying those concepts in the Peruvian legal frame for labor conciliation. At last, the article analyzes the advantages and criticism towards labor conciliation to, finally, underline its importance among labor dispute management.